Relationship between Parental Alienation and Interpersonal Relationships: A Case of Adolescents’ in Selected High Schools in Kiambu County, Kenya - Wanjao , Jane; Njoroge , W; Kamau , Elizabeth (African Journal of Education,Science and Technology (AJEST), 2023)
A conducive environment that is associated with thriving of children enhances parental behaviours towards their children. In family environments, where conflicts abound, each parent strives to absolve himself/herself of being in the wrong by providing explanations to children the meaning of the conflict, and obviously blaming the other marital partner. In this regard, post-divorce parental alienation creates an unfavourable environment which may disorganise the adolescents from adaptive living. The purpose of the study was to examine the relationship between parental alienation and adolescents’ interpersonal relationships among adolescents in selected high schools in Kiambu County, Kenya. PERMA wellbeing theory of flourishing guided this study. The study employed a descriptive survey design. Multistage sampling, comprising of inclusion and exclusion criteria and cluster sampling techniques, which were used to select the 240 adolescents from a population of 3776. Data was collected using Baker strategy questionnaire (BSQ) and the PERMA-Profiler. Descriptive statistics included frequencies and percentages, while Chi-square analysis was used to test for the hypotheses. The computer software SPSS version 25 aided in analysis. The findings revealed that post-divorce parental alienation affects adolescents’ inter-personal relationships. The study recommends that intervention measures be implemented in consideration of factors as follows. Firstly, divorcing parents take an interest in understanding adolescence stage and its challenges. Secondly, parents who are intending to divorce ought to seek counselling services for their adolescents from a mental health practitioner. Lastly, marriage and family therapists should spearhead campaigns for the welfare of children coming from divorced families, the context in which parental alienation takes place.